PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI FPB DAN KPK DENGAN MENERAPKAN MODEL PROBLEM BASED LEARNING (PBL) DAN MEDIA JARIMATIKA KELAS V SD MUHAMMADIYAH 1 SURAKARTA - Choirun Nisa; Jamil Ammar Ghozi; Fikriana, Nisa Inda; Sylviana Ika Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning involves numerical skills, including multiplication. In elementary school, multiplication is typically taught in third grade. However, some fifth-grade students have not yet mastered multiplication, even though this skill is essential for understanding topics such as FPB and KPK, as well as other mathematical concepts. This study aims to examine the improvement in learning outcomes through the implementation of the Problem-Based Learning (PBL) model assisted by jarimatika media in teaching FPB and KPK to fifth-grade students. This research employed Classroom Action Research using two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were 23 students of class VD at SD Muhammadiyah 1 Surakarta. The results showed that the application of the PBL model with jarimatika media improved the learning outcomes of fifth-grade students. In the first cycle, the students' mastery learning level reached 47.82%. In the second cycle, it increased significantly to 86.96%.